2020
DOI: 10.3390/math8050820
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Model for Coronavirus Spread

Abstract: The spread of epidemics has always threatened humanity. In the present circumstance of the Coronavirus pandemic, a mathematical model is considered. It is formulated via a compartmental dynamical system. Its equilibria are investigated for local stability. Global stability is established for the disease-free point. The allowed steady states are an unlikely symptomatic-infected-free point, which must still be considered endemic due to the presence of asymptomatic individuals; and the disease-free and the full e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Some authors [ 16 , 17 ] estimated the mean reproduction number for COVID-19 in the early phase of outbreak, which is slightly higher than that for SARS-CoV. Still other works where the basic reproduction number is estimated for different countries can be found in [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [ 16 , 17 ] estimated the mean reproduction number for COVID-19 in the early phase of outbreak, which is slightly higher than that for SARS-CoV. Still other works where the basic reproduction number is estimated for different countries can be found in [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“…The first term in equation (5) corresponds to horizontal recruitment in the hospitalized human population. The second and third terms represent the arrival of new hospitalized after testing an infectious (at rate (1 − p) q) and disease worsening for quarantined (at rate α 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first group addressed the problem of forecasting the disease in order to help decision makers to better evaluate the logistic challenges they will face [1, 3, 4, 16, 15, 24, 25, 28, 29, 37, 38, 39, 41, 45, 47, 48, 51, 61, 62]. The second category of papers focused on evaluating the effectiveness of mitigations measures prescribed by the WHO and different governments in order to define better fighting strategies [5, 9, 12, 13, 14, 29, 34, 37, 41, 44, 45, 46, 50, 53, 55, 54, 60, 62]. The last set of papers studied the social and the economical impacts of the pandemic [35, 59].…”
Section: Introductionmentioning
confidence: 99%
“…Bentout et al [8] developed an susceptible exposed infectious recovered model to estimation and prediction for COVID-19 in Algeria. Belgaid et al [9] suggested and analysis of a model for Coronavirus spread. Owolabi et al [10] proposed and analyzed a nonlinear epidemiological model for SARS CoV-2 virus with quarantine class.…”
Section: Introductionmentioning
confidence: 99%